2020
DOI: 10.1371/journal.pone.0230392
|View full text |Cite
|
Sign up to set email alerts
|

High-mobility group box 1 fragment suppresses adverse post-infarction remodeling by recruiting PDGFRα-positive bone marrow cells

Abstract: High-mobility group box 1 protein (HMGB1) fragment enhances bone marrow-derived mesenchymal stem cell (BM-MSC) recruitment to damaged tissue to promote tissue regeneration. This study aimed to evaluate whether systemic injection of HMGB1 fragment could promote tissue repair in a rat model of myocardial infarction (MI). Methods HMGB1 (n = 14) or phosphate buffered saline (n = 12, control) was administered to MI rats for 4 days. Cardiac performance and left ventricular remodeling were evaluated using ultrasonogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…For example, Kido et al reported that HMGB1 can prevent deterioration of cardiac function following injection into a hamster model of dilated cardiomyopathy [ 34 ]. Goto et al also reported that this peptide promotes tissue repair in a rat model of myocardial infarction [ 15 ]. Moreover, HMGB1 peptide is being evaluated in clinical trials in Japan (S-005151, Redasemtide) for dystrophic epidermolysis bullosa (phase II) and acute ischemic stroke (phase II).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Kido et al reported that HMGB1 can prevent deterioration of cardiac function following injection into a hamster model of dilated cardiomyopathy [ 34 ]. Goto et al also reported that this peptide promotes tissue repair in a rat model of myocardial infarction [ 15 ]. Moreover, HMGB1 peptide is being evaluated in clinical trials in Japan (S-005151, Redasemtide) for dystrophic epidermolysis bullosa (phase II) and acute ischemic stroke (phase II).…”
Section: Discussionmentioning
confidence: 99%
“…no. AEF93//449-020) was provided by StemRim Inc. (Osaka, Japan) [ 15 ]. Before injection, HMGB1 peptide was dissolved in normal saline (NS, concentration: 1 mg/mL; Otsuka Pharmaceutical Co., Ltd., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…In EB, the major source of HMGB1 is from hypoxic keratinocytes in blister roofs. The key regenerative medicine part of HMBG1 lies within the A box of the protein and its value was demonstrated in col7a1 hypomorphic mice in which intravenous injection of this part of HMGB1 restored C7 and prolonged survival [136][137][138].…”
Section: High Mobility Group Box-1 (Hmgb1)mentioning
confidence: 99%
“…As previously reported [19,20,39] , StemRIM (Osaka, Japan) employed solid-state synthesis to produce the HMGB1 peptide from the MSC mobilization domain of human HMGB1. The synthetic HMGB1 peptide was dissolved in distilled water to a concentration of 1 mg/mL prior to systemic administration.…”
Section: Hmgb1 Peptidementioning
confidence: 99%
“…Our previous work also identi ed and synthesized a critical domain in HMGB1 that induces regeneration. Through increasing PDGFRα + BM-MSCs accumulation in cardiac tissue, the synthesized peptide has therapeutic potential in dilated cardiomyopathy and myocardial infarction [19,20] . Currently, we are evaluating the e cacy of the HMGB1 peptide in a phase II clinical trial for RDEB patients (UMIN ID: UMIN000026645).…”
Section: Introductionmentioning
confidence: 99%